PENGARUH EFEKTIVITAS KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU - Adi Robith Setiana (Universitas Nusa Cendana, 2022)
The purpose of this study were to describe the influence the Leadership Effectiveness and Motivation on teacher Performance in MTs Serba Bakti Suryalaya Boarding School District of Tasikmalaya. The research method uses a quantitative approach. The population is all teachers in MTs Serba Bakti Suryalaya boarding school district of Tasikmalaya as many as 30 teachers. The sampling technique is saturated sample. Data were analyzed using regression analysis. The results of this study finding that there are significant effect partially and simultaneously of Leadership Effectiveness and Motivation on teacher Performance at MTs Serba Bakti Pondok Pesantren Suryalaya Tasikmalaya Thus, the higher the effectiveness of leadership, the better the performance and the higher the work motivation, the better the performance. Keywords: Leadership Effectiveness, Motivation, Teacher Performance